2016
DOI: 10.1038/srep24928
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling activation induces stem cell proliferation and hormone release in the adult pituitary gland

Abstract: Hedgehog (HH) signaling is known to be essential during the embryonal development of the pituitary gland but the knowledge about its role in the adult pituitary and in associated tumors is sparse. In this report we investigated the effect of excess Hh signaling activation in murine pituitary explants and analyzed the HH signaling status of human adenopituitary lobes and a large cohort of pituitary adenomas. Our data show that excess Hh signaling led to increased proliferation of Sox2+ and Sox9+ adult pituitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 51 publications
4
63
2
Order By: Relevance
“…The findings suggest that the SHH pathway regulates adult pituitary stem cell proliferation (Pyczek et al 2016).…”
Section: Sonic Hedgehog: Regulator Of Adult Pituitary Stem Cell Prolimentioning
confidence: 93%
See 3 more Smart Citations
“…The findings suggest that the SHH pathway regulates adult pituitary stem cell proliferation (Pyczek et al 2016).…”
Section: Sonic Hedgehog: Regulator Of Adult Pituitary Stem Cell Prolimentioning
confidence: 93%
“…No significant differences were observed between prolactinomas and normal pituitary tissue. Another study observed SHH production and GLI1 upregulation not only in somatotropinomas (and corticotropinomas), but also in prolactinomas (Pyczek et al 2016). From the studies so far, it may appear that NOTCH and SHH signaling are regulated in opposite ways in the different tumor subtypes.…”
Section: Dysregulation Of Shh In Pituitary Tumorigenesismentioning
confidence: 96%
See 2 more Smart Citations
“…Inducible deletion of the SHH receptor PTCH in adult mouse pituitary causes over-activated SHH signaling, increased proliferation of SOX2- and SOX9-expressing cells, and increased expression of ACTH, GH, and PRL (114). This study also found high SHH and GLI1 expression in ACTH-, GH-, and PRL-expressing human pituitary adenomas, suggesting that SHH activity could be involved in stimulating pituitary stem cells into tumorigenesis.…”
Section: Cell Signaling Pathways Regulating Pituitary Stem Cellsmentioning
confidence: 99%